Altered serum mineral concentrations among pulmonary tuberculosis and its association with Vitamin D, adipokines and inflammatory cytokines - Moideen, Kadar; Gunasekaran, Harinisri; Loukrakpam, Bidyalakshmi; Ahamed, Shaik Fayaz; Nathella, Pavan Kumar; Rajendran, Ananthan; Bethunaickan, Ramalingam; Babu, Subash (Frontiers in Nutrition, 2025)
BackgroundTuberculosis (TB), being the second most killer among infectious diseases remains a major health challenge in many developing countries. Most cases of active TB are due to reactivation of Latent TB Infection (LTBI). Existing evidence suggests that malnutrition can contribute to TB reactivation, by modulating the immune response, along with other factors such as chronic diseases such as Diabetes, HIV, smoking, alcohol use, and aging. Therefore, in order to study the relationship between malnutrition and TB, we analysed the plasma levels of minerals and other inflammatory mediators among PTB, LTBI+ and LTBI− groups.MethodsThe plasma mineral concentrations levels were correlated with cytokines, Vitamin D and other soluble protein data generated from the same cohort. The statistical analyses were performed by applying Kruskal–Wallis test, the Wilcoxon test, principal component analysis (PCA) and Spearman correlation analysis between the parameters.ResultsPTB group showed significant increase in Cu, Cu/Zn, and Cu/Se ratios and lower levels of Se and Zn. After anti-TB treatment (ATT), Cu, Zn, Cu/Se, and Cu/Zn ratios significantly decreased and Se levels increased compared to the baseline. The principal component regression analysis (PCRA) plot depicts Fe levels higher in PTB group than control group whereas the concentrations of other minerals and their ratio are higher in control group than the PTB group thus distinguishing the two groups. The correlation matrix of the PTB group showed several significant correlations. Among the minerals, Cu showed positive correlation with several pro- and anti-inflammatory cytokines. The correlation matrix of the HC group demonstrated a very few correlations.ConclusionThe findings from our study suggest a potential role of circulating minerals in promoting or demoting inflammation by regulating inflammatory cytokines involved in TB. Further studies are required to understand the importance of nutritional intervention in controlling and preventing TB.